Information and Communication Technologies (ICT), At the Service of Knowledge Sharing in Organizations: Case of the Moroccan Banking Sector. - Achraf Nafzaoui, Mohamed; Sebbar, Abdellah; Berdi, Abdelaziz (International Journal of Engineering and Technology, 2019)
Information and Communication Technologies (ICT) are invading all sectors. The economic sector is at the center of the technological revolution, which is in reality an organizational and managerial revolution. This paper examines the role of ICTs in knowledge sharing and seeks to assess the sharing culture among actors in the Moroccan banking sector. A multi-method approach was carried out: administering the questionnaire to a sample of ICT users and conducting semi-structured interviews with a dozen banking players. The results of the study show that ICT is a tool for sharing knowledge and the culture of sharing, which is considered strong among the actors, promotes this practice in Moroccan banks.Â